LanguageScreen: The Development, Validation, and Standardization of an Automated Language Assessment App - Hulme, Charles; McGrane, Joshua; Duta, Mihaela; West, Gillian; Cripps, Denise; Dasgupta, Abhishek; Hearne, Sarah; Gardner, Rachel; Snowling, Margaret (Language, speech & hearing services in schools, 2024)
Oral language skills provide a critical foundation for formal education and especially for the development of children's literacy (reading and spelling) skills. It is therefore important for teachers to be able to assess children's language skills, especially if they are concerned about their learning. We report the development and standardization of a mobile app-LanguageScreen-that can be used by education professionals to assess children's language ability. The standardization sample included data from approximately 350,000 children aged 3;06 (years;months) to 8;11 who were screened for receptive and expressive language skills using LanguageScreen. Rasch scaling was used to select items of appropriate difficulty on a single unidimensional scale. LanguageScreen has excellent psychometric properties, including high reliability, good fit to the Rasch model, and minimal differential item functioning across key student groups. Girls outperformed boys, and children with English as an additional language scored less well compared to monolingual English speakers. LanguageScreen provides an easy-to-use, reliable, child-friendly means of identifying children with language difficulties. Its use in schools may serve to raise teachers' awareness of variations in language skills and their importance for educational practice.